Semi-synthetic Approaches to N-Glycosylation: A Story of Thiol-Ene Methodology, and Interferon-γ - Lynch, Dylan (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
The following thesis, entitled “Semi-synthetic Approaches to N-Glycosylation: A Story of Thiol-Ene Methodology, and Interferon-γ” is composed of six chapters. The first chapter provides an overview of the key concepts that underpin the present work. An outline of post-translation modifications, with a focus on glycosylation, is discussed. The synthetic methods for accessing N-glycopeptides are thoroughly reviewed, with a highlight on radical methods that foreshadows the chapters to come. Bioconjugation and two important ‘click’ reactions are discussed, as is Interferon-γ – a hugely important protein which is central to this work. The thiol-ene reaction is examined in terms of mechanistic detail and versatility, as well as the behaviour of thiyl radicals in their addition to alkenes and alkynes. Finally, the research questions of each forthcoming chapter are posed, with clear aims set out. The first part of this work, Chapter Two, investigates the use of carbohydrate moieties as molecular scaffolds for N-glycopeptide synthesis. A number of S-trityl thioesters are prepared, and reacted with two highly functionalised N-acetyl-D-glucosamines. The propensity of these systems to allow S-to-N acyl transfer is investigated, and a number of anomeric amides are prepared. The mechanistic detail of this reaction is thoroughly analysed, and overall an interesting synthetic methodology is depicted. In Chapter Three, the semi-synthesis of Interferon-γ is described. The incorporation of a non-natural amino acid into the polypeptide backbone is investigated, as well as the bioconjugation of a large mammalian glycan via ‘click’ chemistry. This route is intended to provide access to glycosylated, refolded Interferon-γ in its natural dimeric form. An in-depth analysis of the purification steps, trials and tribulations associated with recombinant protein expression, and future work is discussed in this chapter. Chapter Four introduces a thiol-ene mediated radical methodology for the cyclisation of unsaturated substrates. A serendipitously discovery in the course of supervising an undergraduate researcher is fully investigated in terms of scope, limitations, and utility. A number of unsaturated substrates are prepared, and a diverse array of thioacids are reacted with these materials. A blue-light photoreactor is constructed and investigated as an even milder form of radical initiation, with a detailed analysis of the various visible light photoinitiators that can be employed. ii In Chapter Five, two collaborative projects are discussed, that the author is deeply grateful to have been part of. While these projects culminated in publications centering on the biological properties of these compounds, this brief chapter illustrates the synthetic protocols designed for their syntheses. The first of these projects involves the synthesis of a number of rhamnosides, which were later used by our immunology collaborators in studies regarding Mycobacterium tuberculosis. The second of these collaborations involves the synthesis of a highly functionalised cytotoxic naphthalimides drug, linked to a carbohydrate moiety via a ‘self-immolative linker’, which localises the drug release to tumour tissue. Finally, Chapter Six described the experimental details employed in the course of this research work, and the characterisation of the compounds synthesised within this thesis. A brief appendix, Appendix A, is available at the very end of this thesis, with some select NMR spectra from Chapter Two that the reader may peruse.
APPROVED
Keywords: radical; glycoscience; thiol-ene; thiyl radicals; interferon